Behavioral Disturbances among School Children in Baghdad Province - hussain, Sulaf A .; M, Maliha; Wahid, Salwa S. A. (AL-Kindy College Medical Journal, 2009)
Background: Mental health of children has recently been receiving increased attention in many parts of the world. However, such attention has been lacking in developing countries, particularly in the form of systematic research Aim: The study aimed to find out the frequency of behavior disorders in a sample of primary school children and the different social and demographic factors that might be related to this disorder. Methods: The study is a cross-sectional one that included 918 primary school pupils in both urban and rural areas of Baghdad. Rutter’s questionnaire teacher’s version was used to assess the pupils, and the demographic data was obtained by special questionnaire sent to the parents to be completed. Results: The rate of behavior disorder was found to be 49%, in both rural and urban areas, males had higher prevalence rate than females. The disturbed pupils had higher scholastic failure and their parents of lower educational level and came from highly crowded houses, they had higher rate of disrupted family by either death of one of the parents or their father is married to more than one wife. Conclusion: There is high rate of behavior disturbances in school aged children in Baghdad, associated with low socioeconomic status, bereaved children and having fathers married to more than one wife. The study shows that these children have low scholastic achievement.